Implementation Science for the Practice-Oriented Nurse Leader. Issue 2 (April 2023) - Nelson-Brantley, Heather V.; Chipps, Esther
Abstract : Senior nurse leaders are accountable for improving patient outcomes efficiently and cost-effectively. Nurse leaders often find heterogeneous patient outcomes across comparable nursing units in the same enterprise, presenting a challenge for nurse leaders tasked with making system-wide quality improvements. Implementation science (IS) offers a promising new approach to guide nurse leaders in understanding why certain implementation efforts meet with success or failure and the barriers faced in making practice changes. Knowledge of IS builds upon evidenced-based practice and quality improvement knowledge, adding to the armamentarium of tools at nurse leaders' disposal for improving nursing and patient outcomes. In this article, we demystify IS, differentiate it from evidence-based practice and quality improvement, describe IS concepts every nurse leader should be familiar with, and outline nurse leaders' role in building IS in their organizations.